High‐Saturated‐Fat Diet Increases Circulating Angiotensin‐Converting Enzyme, Which Is Enhanced by the rs4343 Polymorphism Defining Persons at Risk of Nutrient‐Dependent Increases of Blood Pressure. Issue 1 (January 2017) - Schüler, Rita; Osterhoff, Martin A.; Frahnow, Turid; Seltmann, Anne‐Cathrin; Busjahn, Andreas; Kabisch, Stefan; Xu, Li; Mosig, Alexander S.; Spranger, Joachim; Möhlig, Matthias; Hornemann, Silke; Kruse, Michael; et al.
Abstract : Background: Angiotensin‐converting enzyme (ACE) plays a major role in blood pressure regulation and cardiovascular homeostasis. Contrary to the assumption that ACE levels are stable, circulating ACE has been shown to be altered in obesity and weight loss. We sought to examine effects of a high‐saturated‐fat (HF) diet on ACE within the NUtriGenomic Analysis in Twins (NUGAT) study. Methods and Results: Forty‐six healthy and nonobese twin pairs initially consumed a carbohydrate‐rich, low‐fat diet over a period of 6 weeks to standardize for nutritional behavior prior to the study, followed by 6 weeks of HF diet under isocaloric conditions. After 6 weeks of HF diet, circulating ACE concentrations increased by 15% ( P =1.6×10 −30 ), accompanied by an increased ACE gene expression in adipose tissue ( P =3.8×10 −6 ). Stratification by ACE rs4343, a proxy for the ACE insertion/deletion polymorphism (I/D), revealed that homozygous carriers (GG) of the variant had higher baseline ACE concentrations ( P =7.5×10 −8 ) and additionally showed a 2‐fold increase in ACE concentrations in response to the HF diet as compared to non‐ or heterozygous carriers (AA/AG, P =2×10 −6 ). GG carriers also responded with higher systolic blood pressure as compared to AA/AG carriers ( P= 0.008). The strong gene‐diet interaction was confirmed in a second independent, cross‐sectional cohort, the Metabolic Syndrome Berlin Potsdam (MeSyBePo) study. Conclusions: The HF‐diet‐induced increase of ACE serum concentrations reveals ACE to be a potential molecular link between dietary fat intake and hypertension and cardiovascular disease (CVD). The GG genotype of the ACE rs4343 polymorphism represents a robust nutrigenetic marker for an unfavorable response to high‐saturated‐fat diets. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01631123.